Limpeza de feridas: caracterização e validação de protótipo para aquecimento de soro fisiológico e normatização de seu uso em unidades ambulatoriais - Bezerra, Jaqueline Evangelista da Costa (2015)
Although the literature evidence the importance of using heated solution to clean injuries while doing a curative, there is not a safe and accessible procedure to heat solutions for this purpose yet. Objective: Test the efficiency of equipment produced to heat saline solution applied to treat injuries at ambulatory of curative; identify the time to cold the heated saline solution when exposed to the environmental temperature. Objective: Test the efficiency of equipment produced to heat saline solution applied to treat injuries at ambulatory of curative; identify the time to cold the heated saline solution when exposed to the environmental temperature. Method: Experimental study of technological innovation accomplished in three stages: the prototype development; efficiency test of heating saline solution flacons; instruction of the using time of the heated solutions. Result: It was developed three prototypes: one of heating by means of Peltier cells, other one of heating by resistance and another one by electromagnetic irradiation, with different results regarding the efficiency.The time of cooling varied from 3 to 35 minutes, depending on the inicial heating,the size of the flacon and the type of wrapper Conclusion: The prototype that best complied with the purpose of safe heating of the solutions was the adapted microwave by reverse engineering, from parameters of standardization created at this research. The prototype was efficient to heat flacons except the 100-ml -tough wrapper flacon which did not reach the expected temperature, however it does not derail its use at wounds treatment. The heated solutions presented time of use differed in relation to the volume of the flacons. At clinical practice can be recommended the use of the flacons of 100 ml to 250 ml per 10 minutes ( except the 100- ml- tough flacon, which is 3 minutes) and of 20 minutes for larger flacons.